Preschool teachers provide fewer participation opportunities to working-class students than those from more privileged backgrounds - Lewis Doyle; Andrei Cimpian; Louise Goupil; Sébastien Goudeau (Proceedings of the National Academy of Sciences, 2025)
Social class disparities exist from the earliest stages of education. Research has suggested that class-based differences in factors such as socialization practices and access to resources partly explain this phenomenon, but less work has explored whether teachers’ practices also exacerbate these inequalities. Using whole-class observations of 63 preschool classroom discussions ( N = 226 students, 10 teachers), we coded 7,941 student participation attempts and subsequent responses from teachers. Mixed-effects Bayesian logistic regressions showed that whether students played by the rules by raising their hands or broke the rules by calling out, they were less likely to have their participation attempts accepted if they came from a working-class background, even when their perceived language skills were matched to their middle- and upper-class peers. These results suggest that early schooling experiences may serve to exacerbate inequalities rather than level the playing field.